2014
DOI: 10.1186/1742-2094-11-125
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR kinase inhibitors polarize glioma-activated microglia to express a M1 phenotype

Abstract: BackgroundIncreased activation of mammalian target of rapamycin (mTOR) is observed in numerous human cancers. Recent studies on the glioma kinome have identified several deregulated pathways that converge and activate mTOR. The available evidence on the role of microglia in CNS cancers would suggest a dual role, a tumoricidal role and -on the contrary- a role favoring tumor growth.MethodsIn the present paper, we have compared the effects of μM concentrations of rapamycin (RAPA) and its analog, RAD001 (RAD), on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 36 publications
3
46
1
Order By: Relevance
“…However, the effects of rapamycin-induced autophagy on microglial activation remain elusive and controversial. Rapamycin has been reported to inhibit microglial activation for functional recovery after spinal cord injury, 67 contribute to glioma-induced microglial activation through polarizing its M1 phenotype, 68 or have no effect at all on microglial activation in rat models of temporal lobe epilepsy. 69 These inconsistencies could be attributable to the different disease models or the different doses of rapamycin used.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of rapamycin-induced autophagy on microglial activation remain elusive and controversial. Rapamycin has been reported to inhibit microglial activation for functional recovery after spinal cord injury, 67 contribute to glioma-induced microglial activation through polarizing its M1 phenotype, 68 or have no effect at all on microglial activation in rat models of temporal lobe epilepsy. 69 These inconsistencies could be attributable to the different disease models or the different doses of rapamycin used.…”
Section: Discussionmentioning
confidence: 99%
“…As such, glioma-derived M-CSF induces a shift of microglia and macrophages toward the M2 phenotype, which increases tumor growth 56 . Similarly, mTOR 57 or CSF-1 (ref. 56) inhibition shifts to the M1 phenotype.…”
Section: Tams and High-grade (Malignant) Gliomamentioning
confidence: 99%
“…GAMs actively support tumor growth, e.g. In addition, recent studies using glioma mouse models have shown that GAMs-directed therapeutic approaches can be beneficial for disease intervention (Kees et al, 2012;Lisi et al, 2014;Markovic et al, 2011;Pyonteck et al, 2013;Sarkar et al, 2014;Xu et al, 2014). In addition, recent studies using glioma mouse models have shown that GAMs-directed therapeutic approaches can be beneficial for disease intervention (Kees et al, 2012;Lisi et al, 2014;Markovic et al, 2011;Pyonteck et al, 2013;Sarkar et al, 2014;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%